2020
DOI: 10.1007/s00253-020-10973-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria associated with cockroaches: health risk or biotechnological opportunity?

Abstract: Cockroaches have existed for 300 million years and more than 4600 extant species have been described. Throughout their evolution, cockroaches have been associated with bacteria, and today Blattabacterium species flourish within specialized bacteriocytes, recycling nitrogen from host waste products. Cockroaches can disseminate potentially pathogenic bacteria via feces and other deposits, particularly members of the family Enterobacteriaceae, but also Staphylococcus and Mycobacterium species, and thus, they shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 174 publications
(235 reference statements)
6
47
0
1
Order By: Relevance
“…The rapid emergence of antibiotic resistance among human and animal pathogens represents a major health threat. It is projected that by 2050, infections from antibiotic-resistant pathogens will exceed ten million cases [ 15 , 42 , 43 , 44 ], which will increase the cost of treatment and require longer hospitalizations. The emergence of this resistance to most conventional antibiotics has forced researchers to look for new promising alternatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid emergence of antibiotic resistance among human and animal pathogens represents a major health threat. It is projected that by 2050, infections from antibiotic-resistant pathogens will exceed ten million cases [ 15 , 42 , 43 , 44 ], which will increase the cost of treatment and require longer hospitalizations. The emergence of this resistance to most conventional antibiotics has forced researchers to look for new promising alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Miroslava et al 2020 isolated and identified the gut bacteria of Apis mellifera and evaluated its antagonistic effect against Paenibacillus larvae, which causes American foulbrood (AFB) in honeybees [ 48 ]. The results of Guzman and Vilcinskas [ 15 ] revealed that the gut bacteria of cockroaches produce active molecule(s) with potent antibacterial properties. In their specific niches, microorganisms compete for nutrients and space by producing defensive molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the literature reveals that AAB are prominent members of insect gut microbiota. Most reports concerning cockroach-associated bacteria refer to pathogens, but cockroaches also harbour diverse non-pathogenic bacteria that may be useful in biotechnology as a source of novel enzymes or specialized metabolites [21]. Here we report the isolation and description of a proposed new genus of the family Acetobacteraceae , isolated from the gut of the Madagascar hissing cockroach Gromphadorhina portentosa .…”
Section: Full-textmentioning
confidence: 98%
“…Following the capture of the host insects or animals such as cockroaches and flies, the microorganisms can be isolated using classical methods (e.g., washing with saline water) and then subjected to standard protocols for antimicrobial susceptibility testing [ 32 , 33 , 39 , 40 , 55 , 56 , 57 ]. To identify antibiotic susceptible microorganisms or ARB in a sample, the minimum inhibitory concentrations (MIC) of antibiotics to particular bacteria are predefined [ 58 ].…”
Section: Antimicrobial Resistancementioning
confidence: 99%